TINDAK TUTUR KOMISIF PEMENTASAN DRAMA â€œMANGIR WANABAYAâ€ (ANALISIS SOSIOPRAGMATIK) - Wicaksono, Andri; Hastuti, Hastuti (LPPM STKIP PGRI Bandar Lampung, 2014)
This study aims to describe the shape and the social context of utterances used to express speech acts commissive intend, promise, swear, and bernadar in staging dramas Mangir Wanabaya. This study uses a pragmatic approach and sociolinguistics, hereinafter referred sosiopragmatik approach. Problem to be investigated is the use of the form and context in speech acts commissive.The form of this research is descriptive qualitative. The strategy used in this study was content analysis. Collection data techniques is to study the document. Research data collection, namely the context of noting that the use of natural language in order to reveal the intention of utterances commissive appropriately.The research proves that this form of speech acts commissive Mangir Wanabaya drama performances can be said, propositif predicate, and the context of the stated commissive. Pragmatics in the context of the study can be used as guidance for recognizing intent. Obtained commissive speech act is intended commissive speech acts, speech acts commissive promise, swear commissive speech acts, speech acts commissive bernadar.